2017
DOI: 10.1097/md.0000000000008516
|View full text |Cite
|
Sign up to set email alerts
|

Case report

Abstract: Rationale:Neurosarcoidosis (NS) is an uncommon manifestation of systemic sarcoidosis, with a propensity for middle-agedwomen. Often discovered only at autopsy, rates of neurologic involvement (5%–10%) reported in the literature underscore a lack of sensitivity and specificity in current diagnostic methods.Patient concerns:Herein, we describe a 53-year-old woman who presented with gait imbalance and distal extremity muscular weakness. She was known to harbor a brain mass (4 years in duration) that was monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…However, in one research, steroid-resistant neurosarcoidosis which failed to respond to infliximab alone responded to the addition of IVIG to the regimen. In different presentations of the neurosarcoidosis, such as multiple conduction blocks and small fiber neuropathy, which were resistant to first-line and second-line therapeutic agents responded to IVIGs [9]. Our patient responded very well to the addition of IVIG supporting the result of other reported cases [7,10].…”
Section: Discussionsupporting
confidence: 80%
“…However, in one research, steroid-resistant neurosarcoidosis which failed to respond to infliximab alone responded to the addition of IVIG to the regimen. In different presentations of the neurosarcoidosis, such as multiple conduction blocks and small fiber neuropathy, which were resistant to first-line and second-line therapeutic agents responded to IVIGs [9]. Our patient responded very well to the addition of IVIG supporting the result of other reported cases [7,10].…”
Section: Discussionsupporting
confidence: 80%
“…Neurosarcoidosis presents symptoms such as meningitis, seizures, neuroendocrine symptoms, and neuropsychiatric symptoms (4).…”
Section: Introductionmentioning
confidence: 99%
“…Data on the disease burden of sarcoidosis in Ghana is not readily available. However, a number of cases have been reported such as that by Bajantri et al who reported on a 53-year-old woman with neurosarcoidosis [ 4 ] and two cases of cardiac sarcoidosis in a 51-year-old man and a 58-year-old woman reported by Afriyie-Mensah et al [ 5 ]. It is more common in females [ 1 ], and the age at diagnosis is usually between 40 and 55 years [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation